European Union Strategy for COVID-19 Vaccines - de Farmacoterapia, Revista Portuguesa (2020)
The European Commission presented in June 2020 a European strategy to accelerate the development, manufacture and administration of vaccines against COVID-19. This section describes a brief summary of the document, which can be consulted in full at: https://ec.europa.eu/info/sites/info/files/communication-eu-strategy-vaccines-covid19_en.pdf.